A Communication Universe: Manifestations of Meaning, Stagings of Significance - Klyukanov, Igor E. (Lexington Studies in Political Communication Series, 2010)
A Communication Universe offers a new approach to theorizing the nature of communication which is conceptualized as transformations of a space-time continuum of meaning. Igor E. Klyukanov also shows how each transformation can be best discussed in terms of certain theories of communication. Thus, the book is dedicated to both ontological and epistemological issues of communication.
https://katalog.adlr.link/Record/76-EBC662247